Sociodemographic criteria and quality of life among pregnant women with anxiety prior to childbirth - El-Hameed, Nadia A.; A. Ahmed, Zamzam; Fouly, Howieda; Abbas, Ahmed (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Aim: To determine the sociodemographic criteria, quality of life and its relation to level ofanxiety prior to childbirth. Study design: Was a descriptive analytical study. A sample size of162 was estimated to be necessary to achieve a power of 80%. Setting: The data collected fromchildbirth ward at Women’s Health Hospital from February 2015 to May 2015.Tools of thestudy: Three tools were used 1) Demographic & clinical data 2) Anxiety scale by El- Hams(2010), and 3) Quality of life questionnaire by El- Hams (2010). Results: The total number ofparticipants was 162 with mean age 26.7+6.6. More than fifty percent of participants were hadsevere anxiety related to vaginal examination, and the relation between quality of life andchildbirth anxiety confirmed that there was a statistically significant difference. Conclusion:Anxiety level in our study confirm a higher level than comparable studies which reflected anachievement of supposed hypothesis that anxiety level might be thirty percent or greater.Recommendations: The women’s health facilities should include anxiety level test as one ofchildbirth procedures and providing family support system for mother during childbirth process